A case of celiac disease presenting with celiac crisis: rare and life threatening presentation - Rakshya Poudyal; Saroj Lohani; William B. Kimmel (Greater Baltimore Medical Center, 2019)
A 20 year old male with past medical history of Type 1 Diabetes and Hypothyroidism presented to our hospital with severe hypocalcemia. His calcium was 5.8 mg/dl (normal range 8.6-10.3 mg/dl). He had been complaining of generalized weakness for weeks. Vital signs were within normal limits. Physical exam was significant for positive Chvostek sign. Other labs revealed low magnesium, low potassium, low vitamin D, low albumin, metabolic acidosis and low ferritin. He was started on supplements. Tissue transglutaminase antibody IgG was elevated. Upper gastrointestinal endoscopy showed scalloped and blunted duodenal mucosa. Duodenal biopsy showed villous blunting with intraepithelial lymphocytosis suggestive of celiac disease. He was started on gluten free diet. His symptoms improved and he was discharged home. Celiac disease can present in fulminant form with hemodynamic instability and is called celiac crisis. Celiac crisis is usually manifested by severe gastrointestinal manifestations, hypoproteinemia and metabolic and electrolyte disturbances requiring hospitalization. It is diagnosed by criteria proposed by Jamma et al. Celiac crisis is a rare presentation of celiac disease and is associated with high morbidity and mortality. Most of the cases respond to gluten withdrawal and nutritional suport and few require steroids. Abbreviation: Type 1 DM -Type 1 Diabetes Mellitus